Entrepreneurial marketing in action: multidimensional impact and sectoral applications - Quintero-Arango, Luis Fernando; Betancur-Arias, Juan Diego; Machado, Cristiano; Rojas-Quiceno, Guillermo (Clío América, 2024)
This article aims to identify the dynamics of scientific production on Entrepreneurial Marketing (EM) and its influence on organizational performance; researchers conducted two consultations for this objective, one in Scopus and another in Web of Science. The results showed that in the last seven years, there has been a 52 % growth in scientific production, highlighting its importance in the academic and business worlds. Researchers identified three major trends; the first concerns the various metrics used to measure the dimensions of EM, the second pertains to applications of EM in different contexts, and the third involves the theoretical foundations of EM. This study benefits researchers seeking a better understanding of EM, entrepreneurs who desire a straightforward introduction to the subject from a scientific perspective, and educators wishing to integrate the topic of EM into their courses.